Hepatitis C virus drives the pathogenesis of hepatocellular carcinoma: from immune evasion to carcinogenesis. Issue 10 (7th October 2016) - Canavese, Miriam; Wijesundara, Danushka; Maddern, Guy J; Grubor‐Bauk, Branka; Hauben, Ehud
Abstract : Persistent hepatitis C virus (HCV) infection is associated with high incidence of hepatocellular carcinoma (HCC), the most common primary malignancy of the liver with over half a million new cases diagnosed annually worldwide. The aryl hydrocarbon receptor (AhR) is a ubiquitously expressed transcription factor and its activation by environmental chemicals and by its endogenous ligand kynurenine (Kyn) has been implicated in a variety of tumour‐promoting processes such as transformation, tumorigenesis and in immunosuppression that enables tumour survival and growth. Kyn is generated constitutively by human tumour cells via tryptophan (Trp)‐2, 3‐dioxygenase (TDO), a Trp‐degrading enzyme expressed in liver, brain and cancer cells. Notably, it has been shown that TDO‐derived Kyn suppresses anti‐tumour immune responses, thus promoting tumour‐cell survival through activation of the AhR pathway. In the context of HCV infection‐associated HCC, it was shown that AhR signalling is increased in HCV‐infected hepatocytes, and that modifications in the expression of AhR pathway‐specific genes are associated with the progression of HCV infection into HCC. Based on these observations, we present and discuss here the hypothesis that HCV infection promotes HCC by modulation of the TDO–Kyn–AhR pathway, resulting in tumorigenesis as well as in suppression of both anti‐HCV and anti‐tumour immune responses. Hepatitis C infection: A mechanistic model for subsequent liver cancer: A model suggesting how hepatitis C virus (HCV) evades host immunity could lead to drugs that reduce risk of chronic infection and liver cancer. This virus causes hepatocellular carcinoma (HCC) while also exerting a poorly defined inhibitory effect on immune cells, allowing tumors to grow unhindered. Researchers led by Ehud Hauben at The Basil Hetzel Institute for Translational Health Research in Australia hypothesize that HCV‐induced HCC is strongly related to a recently discovered critical link between crucial immunoregulatory mechanisms underlying immunosuppression, tolerance, and immunity. They summarise previous evidence indicating that HCV stimulates enzymatic processes in the liver that convert tryptophan into kynurenine, which in turn switches on the immunosuppressive aryl hydrocarbon receptor (AhR) pathway. Based on the most current findings linking these pathways to tumor growth and progression, they propose a mechanistic model for HCV‐induced HCC. If this model is valid, then blocking tryptophan conversion could help the immune system prevent chronic infection and its consequences.